Mammary fibroadenomatoid hyperplasia in a heifer - Lorena Ferreira Silva (Ciência Rural)
ABSTRACT: This manuscript described the anatomopathological and immunohistochemical findings in a rare case of mammary fibroadenomatoid hyperplasia in a 12-month-old Holstein heifer. A yellow, multilobulated, firm 20cm x 9cm x 6.5cm mass affecting the right quarters of the udder was observed. Total mastectomy was performed. Microscopic evaluation revealed severe hyperplasia of the mammary epithelium and numerous well-differentiated and mildly pleomorphic acini. Additionally, moderate proliferation of the fibrous connective tissue and the myoepithelial cells near the proliferating acini was evident. About 50% of the proliferating epithelial cells showed positive nuclear labeling for estrogen and progesterone receptors, and approximately one-third were positive for Ki-67. In addition, the myoepithelial cells exhibited diffuse nuclear immunoreactivity for p63. Based on the clinical, morphologic, and immunohistochemical findings, a diagnosis of mammary fibroadenomatoid hyperplasia with probable influence of ovarian steroids was made.